Breast cancer screening in postpartum mother: A literature review - Rahmawati, Dwi; Dona, Sismeri; Mahdiyah, Dede; Budiwinata, Winarta; Widodo, Hariadi (Ananda - Health & Education Foundation, 2025)
Background: Breast cancer remains a leading cause of morbidity and mortality among women, with early detection playing a critical role in improving outcomes. Postpartum mothers face unique challenges related to breast cancer screening due to physiological changes in breast tissue, lactation, and competing demands of infant care. Objective: This literature review explores breast cancer screening practices in postpartum mothers, identifies barriers and facilitators, and proposes strategies to improve screening uptake during this critical period. Method: A narrative review was conducted by analyzing studies from peer-reviewed journals. Articles were selected based on their relevance to breast cancer screening, postpartum mothers, and early detection methods. The data were synthesized to highlight key findings, identify gaps, and provide actionable insights. Results: Postpartum mothers experience significant barriers to breast cancer screening, including hormonal changes, lactation-related conditions, and limited awareness. Physiological remodeling of breast tissue can obscure early symptoms, delaying diagnosis. Despite these challenges, self-breast examination (BSE) and acupressure are effective techniques for early detection and breast health improvement. Studies show that BSE reduces mortality by up to 20%, while targeted acupressure enhances lactation and breast tissue awareness. Healthcare provider interventions, such as counseling and education during postpartum visits, improve screening adherence. Conclusion: Breast cancer screening during the postpartum period is essential yet underutilized. Tailored education and integrated care approaches are critical to overcoming barriers and enhancing awareness among postpartum mothers. Further research should explore innovative technologies and interventions to optimize early detection in this population.